Modeling and control of objects with distributed parameters with not complete information: Modeling and control of objects with distributed parameters with not complete information - Yakubov, S.Kh.; Pirova, R.K. (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract: The paper presents the results of research on the development of a mathematical model and an automatic control system with observing devices that provide the necessary microclimate in vegetable stores, which have very high efficiency indicators